(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
In our research we estimate the elasticity of substitution post-communist economies integrated in European Union. There are many approaches to estimate the production function coefficients as the elasticity of substitution. We argue that a frequency panel model is suitable econometric tool for our purposes. We derive the specification from the capital demand first-order condition of firm maximising its profit. Data are adapted from the World Penn Tables and World Development Indicators, World Bank. Data are modified with band-pass filter to abstract them from the business cycles and the short-term effects driven by different underlying processes. The filter creates overlapping observations, the stochastic term is serially correlated and therefore feasible generalized least squares estimator is used. Comparing the results with the relevant results in a world literature we estimate relatively low value of the elasticity of substitution in European post-communist countries. Possible explanations are discussed. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.